Patient safety when practicing a physiotherapist - Mikos, Marcin; Curyło, Mateusz; Juszczyk, Grzegorz; Czerw, Aleksandra Izabela (Journal of Education, Health and Sport, 2017)
Patient safety is a key criterion for assessing the medical profession. In addition to well-established theory and practice in the field of the safety of medical services provided by physicians and nurses, this is a new issue for medical professions that have recently gained professional independence. They belong to the profession of a physiotherapist who obtained professional independence under the Physiotherapist’s Act of 25 September 2015 [1]. The law has adopted innovative patient safety solutions that will be analyzed in this publication. Their performance is supervised by a professional body of physiotherapists entitled to exercise proper care over the profession. The paper analyzes the law governing the practice of physiotherapist profession in the area of patient safety solutions, in particular the right to refuse to perform a medical order and to observe the safety rules in the exercise of the physiotherapist profession as well as the use of the denial and denunciation of events that compromise the patient’s safety. An analysis of case law in patient safety assurance has also been carried out.